Janus MoSSe Nanotubes: Tunable Band Gap and Excellent Optical Properties for Surface Photocatalysis. Issue 10 (1st August 2018) - Tang, Zhen‐Kun; Wen, Bo; Chen, Mingyang; Liu, Li‐Min
Abstract: Transition metal chalcogenides have attracted considerable attention because of their wide applications in solving energy and environmental problems. Here, the electronic structures and optical properties of Janus MoSSe nanotubes are explored by first‐principles calculations. It is shown that the Janus MoSSe nanotubes exhibit versatile electronic properties. All zigzag MoSSe nanotubes exhibit a direct band gap with a good optical absorption. More interestingly, the electronic structure of the armchair MoSSe nanotubes is greatly dependent on the radius. The nanotubes are indirect semiconductors at a small radius of 7.4 Å, and they could gradually become direct semiconductors with the increase of the radius of armchair MoSSe nanotubes. Further, the optical absorption abilities of the armchair MoSSe nanotubes can be further modulated by axial stress. The suitable band gap, lower formation energy, and tunable band gap of the armchair MoSSe nanotubes enable them to have great potential applications for optoelectronics and photocatalysis as low‐dimensional nanomaterials. Abstract : The electronic structures and optical properties of Janus MoSSe nanotubes are explored by first‐principles calculations. It is shown that the Janus MoSSe nanotubes exhibit versatile electronic properties. The electronic structure of the armchair MoSSe nanotubes is greatly dependent on the radius. Besides, optical absorption abilities of armchair MoSSe nanotubes can be further modulated by axial stress.